Transnational radicalism and the connected lives of Tom Mann and Robert Samuel Ross - Kirk, Neville, 1947- (Liverpool University Press, 2017)
A pioneering study of the neglected transnational activities and influences of two important, connected socialists, British-born Tom Mann (1856-1941) and Australian-born Robert Samuel 'Bob' Ross (1873-1931).
Keywords: Mann, Tom, -- 1856-1941.; Ross, R. S.; Mann, Tom, -- 1856-1941; Socialists -- Biography.; Socialism -- History -- 20th century.; HISTORY -- General.; Socialism; Socialists; 1900-1999; Biographies; History